2018
DOI: 10.1021/acs.est.7b05981
|View full text |Cite
|
Sign up to set email alerts
|

Parabens and Their Metabolites in Pet Food and Urine from New York State, United States

Abstract: The exposure of pets, such as dogs and cats, to a wide range of chemicals present in the indoor environment and the concomitant increase in noninfectious diseases in these companion animals are a concern. Nevertheless, little is known about the sources and pathways of exposure to chemicals in pets. In this study, we determined the concentrations of parabens in commercially available cat and dog foods as well as in urine samples from these pets collected from the Albany area of the state of New York in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The age- and gender-related differences in PFAS concentrations in pet feces were described only for those compounds that were detected in more than 60% of the samples (Table ). We categorized dogs and cats into three different age groups for the comparison of concentrations [(i) young, ≤2 years; (ii) adult, >2–5 years; (iii) old, ≥5 years], according to a previous study . There were no significant differences in fecal PFAS concentrations among the three age groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The age- and gender-related differences in PFAS concentrations in pet feces were described only for those compounds that were detected in more than 60% of the samples (Table ). We categorized dogs and cats into three different age groups for the comparison of concentrations [(i) young, ≤2 years; (ii) adult, >2–5 years; (iii) old, ≥5 years], according to a previous study . There were no significant differences in fecal PFAS concentrations among the three age groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The relationship between advanced age and the development of hyperthyroidism might be explained, among other things, by the longer exposure to the substances that potentially act as endocrine disruptors, or by the simple fact that pathological thyroid changes related to hyperthyroidism are consequences of the aging process. As for the sex distribution, in contrast to the researches from New Zealand [4] and a London [12] which identified a higher predisposition for hyperthyroidism in females, the present study showed no significant difference in gender exposure in the studied population, in agreement with previous studies performed in the Ireland, the United Kingdom and Hong Kong [1,10,13]. However, the greater percentage of females in certain studies may represent a bias since eventually the females are more likely to reach an advanced age in relation to males due to the habits of the latter.…”
Section: Journal Of Endocrinology and Thyroid Research Discussionmentioning
confidence: 88%
“…Parabens, in their turn, are used as preservatives for various products, including cosmetics. Just over a decade ago, the effects of these products on the thyroid were not investigated, but the interest in this subject is increasing and researchers are beginning to develop studies in this direction [12,19]. Recently, a study analyzed 60 urine samples from dogs and cats and demonstrated that parabens metabolites, notably benzoic acid and 4-hydroxybenzoic acid, were the most abundantly detected chemicals.…”
Section: Journal Of Endocrinology and Thyroid Research Discussionmentioning
confidence: 99%
“…In one study in New York State, parabens were found in all samples of dog (n=23) and cat (n=35) food and all urine samples from 30 dogs and 30 cats (n=30) (Karthikraj et al . 2018). Dry foods contained higher levels than wet food.…”
Section: Additives Associated With Safety Issues In People and Animal Species Other Than Dogs And Catsmentioning
confidence: 99%